Health-related behaviors of participants and non-participants in a workplace physical activity program. DOI: 10.5007/1980-0037.2011v13n2p131 - Antonio Jose Grande; Mathias Roberto Loch; Evanil Antonio Guarido; João Bruno Yoshinoga Costa; Gabriela Claudino Silva; Felipe Fossati Reichert (Universidade Federal de Santa Catarina, 2011)
The aim of this study was to determine the prevalence of health-related behaviors among workers participating or not in a workplace physical activity program (WPA) at Universidade Estadual de Londrina. Twenty sectors of the university campus participating in the WPA program were randomized. A total of 373 questionnaires were handed out and 334 (89.5%) completed questionnaires were returned. Descriptive statistics and the chi-square test were used for data analysis. Participants in the program presented a lower prevalence of physical inactivity during leisure time (49.3%) and alcohol abuse (17.2%) than non-participants (63.4% and 25.8%, respectively). The frequency of physical inactivity during leisure time, smoking and negative perception of stress was lower among male participants. However, the frequency of insufficient consumption of fruits (52.6% of non-participants versus 72.1% of participants) and vegetables (29.9% of non-participants versus 49.2% of participants) was lower among non-participants. Female participants reported less dissatisfaction with work colleagues (2.2% of participants versus 9.3% of non-participants.) The prevalence of physical inactivity and alcohol abuse was lower among WPA participants, but no significant differences were observed for the other variables. More comprehensive interventions should be implemented in order to reduce the prevalence of risk behaviors among workers.